Potential for Developing Access to Safe Drinking Water in the Highlands Area (Case Study: Bogor City, Indonesia) - Mufida, Ristya Farah; Martono, Dwi Nowo; Gusdini, Ninin (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
The need for water in Indonesia is not directly proportional to its availability. This challenge is not limited to rural areas but also affects urban areas like Bogor City. Since 2004, Regional drinking water company of Bogor City has been classified as healthy and is a pilot city for the prime drinking water zone program alongside two other Indonesian cities. This research aims to assess Bogor City's potential for safe drinking water development, considering the physical environment, readiness of the drinking water system, social conditions, and economic conditions of the community. The methodology used is mixed with a quantitative approach via spatial analysis. The physical environment variable yielded 4 classifications: high potential, potential, moderate potential, and low potential. The very potential classification was dominant in 45 sub-districts. The drinking water system readiness had 4 classifications: potential, moderate potential, low potential, and no potential, with the moderate potential dominating in 51 sub-districts. The community social condition had 4 classifications: potential, moderate potential, low potential, and no potential, with the low potential dominating in 36 sub-districts. The community economic condition variable resulted in 4 classifications. Moderate potential dominates in 29 sub-districts. Bogor City has moderate potential for developing access to safe drinking water. The key factors for this classification are the community's social and economic conditions, as well as the drinking water system's readiness.